THE USING OF CHATGPT IN DEFORMITY OF ESP MATERIAL FOR HEALTH STUDENTS IN THE HIGHER EDUCATION - Triana, Neni; Anita, Fenny (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The use of ChatGPT in developing teaching materials can be used to adjust the needs of ESP teaching materials. Artificial Intelligence (AI) in education has brought significant changes, especially in the development of English for Specific Purposes (ESP) materials. This study explores the use of ChatGPT, a generative AI tool, in redesigning and supporting the creation of ESP learning content for health students in higher education. Using a qualitative literature study approach, this study examines the opportunities, benefits, and challenges in implementing ChatGPT in the ESP context. The results of the study indicate that ChatGPT offers several advantages, such as time efficiency in material development, the ability to adjust content to learners' needs, support for interactive and contextual learning, and assistance in the assessment process. However, there are also challenges such as the potential for inaccurate information, limitations in sensitivity to certain areas, and the need for human validation. This study concludes that although ChatGPT cannot replace the role of educators, this technology can be a valuable tool in modern ESP teaching in the health field. Further empirical research is needed to evaluate the long-term impact on students' learning outcomes and professional language competencies.